Financial Variables and the Conduct of Monetary Policy - Charles Goodhart; Boris Hofmann (Sveriges Riksbank, 2000)
This paper analyses the role of financial variables in the conduct of monetary policy. In the baseline model for the analysis of interest rules, the inflation rate depends on the output gap, which is solely determined by its own lags and the lagged short-term real interest rate. However, from a theoretical point of view there are several other financial variables which may affect aggregate demand, and should therefore be taken into account in the estimation of an output gap equation. In order to assess the importance of financial variables such as asset prices and monetary aggregates for aggregate demand, we estimate a small structural model for 17 developed countries using quarterly data spanning 1973 - 1998. The results indicate that the effect of other financial variables, especially property and share prices, on the output gap is highly significant. It appears that in almost all of the countries in our data set it is necessary to control for the effect of other financial variables on the output gap in order to find a significant effect for monetary policy.
Keywords: E50; 330; Monetary policy; Financial Variables